The Feasibility Analysis of Nipa Palm (Nypa fruticans) Shoot Processing Business in Aceh Singkil Regency - Ibrahim, T. Miftah; Atikah, Qhisthina; Ariska, Nana (Jurnal Agriuma, 2025)
This study aims to analyze the technical and financial feasibility of the nipa shoot processing business in Singkil District, Aceh Singkil Regency. This study employed a quantitative descriptive approach, incorporating production and financial analyses based on direct observation, in-depth interviews, and measurements of production parameters. Financial feasibility was evaluated using the Break-Even Point (BEP), Return on Investment (ROI), Payback Period (PBP), and Benefit–Cost Ratio(B/C) indicators. The results indicate that the nipa shoot processing business, with a capacity of 600 stems per day, has high production efficiency, with a recovery rate of 43%. From a financial perspective, the business is highly feasible, requiring a total capital investment of IDR 122,080,000 and generating a projected annual net profit of IDR 785,025,000. Feasibility indicators show a benefit-cost ratio of 3.345, a return on investment of 861.9%, and a payback period of 0.116 years. Sensitivity analysis proved the business resilience against market volatility. The Nipa shoot processing business is feasible for development as a sustainable and highly profitable business model.